Internetowy serwis samorządowy – ewolucja przekazu w okresie „mobilnej zmiany” - Kowalik, Krzysztof (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The Internet is changing not only the functioning of the commercial media, but also local government media (issued, created by local governments, understood as offices, and not social organizations, local, etc.). The opportunity has arisen for municipalities to expand their communication with residents, tourists, investors through publications on their websites. They need to adapt to network media. To do this, local governments are creating their own editorial teams to prepare content to meet the needs of their customers, who are increasingly using mobile devices. Based on my own research I have tried to identify the environment of the media of local governments, what content they prefer (agenda topics), the tasks to be fulfilled by a municipal, urban contemporary website, and who creates it. An important element is preparing media for mobile devices, the use of which has a strong upward trend.